Bipolar versus unipolar energy in the surgical ablation of atrial fibrillation in patients with mitral valve surgery - Leonardo Canale; Bruno Azevedo; Marcelo Goulart Correia; Ernesto Chavez; Erica Macedo; Cintia Mattoso; Roberta Lima; Juliana Vieira; Cristiane C. Lamas; Clara Weksler (Heart Vessels and Transplantation, 2018)
Objective: To evaluate the presence of sinus rhythm or atrial fibrillation (AF) in patients who had mitral valve surgery with concomitant surgical ablation of AF, by unipolar or bipolar radiofrequency.